Wybrane przypadki obfitych opadów śniegu w Poznaniu - Bednorz, Ewa (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
Composite maps of the sea level pressure and 500 hPa geopotential heights means and anomalies were constructed for the days with the high snow accumulation in Poznań. Similar maps of the air temperature at the isobaric level 850 hPa and of precipitable water content were presented. Additionally, 48-hours back trajectories of air masses for chosen days with the most effective snowfalls were constructed, using the NOAA HYSPLIT model. Negative anomalies of sea level pressure and 500 hPa heights, which mean low pressure systems spreading over Europe, are the basic condition of abundant snowfalls in Poznań. Snowfalls may appear as a result of fronts in the colder parts of Mediterranean cyclones with the dynamic warm and humid air of distant southern origin climbing upwards on the cooler and more stabile polar air masses from the north or east. The alternative location of snow-bringing low pressure systems is the Baltic Sea region.
Keywords: snowfalls in Poland; air circulation; synoptic conditions; back trajectories